Collecting Livestock Data : A Snapshot of Survey Methods - World Bank (Washington, DC, 2014)
The design, implementation, and monitoring and evaluation of livestock sector public and private sector investments are based on evidence and information generated by a multitude of data collection systems, including regular and one-off, or ad-hoc, surveys. This note reviews the major survey methods that are regularly implemented by developing country governments, including: the agricultural and livestock census; agricultural and livestock sample surveys; household budget surveys; living standards measurement studies; administrative records or routine data; and others, such as the population and housing census and labor surveys. It identifies the major livestock-related indicators that the various surveys for which the prime target rarely is livestock are likely to generate. Understanding these data sources is critical for decision makers to make appropriate use of available data and indicators, and is the first step in designing and setting up a comprehensive livestock data collection system. The note concludes by highlighting that a system of livestock statistics must be seen as part of a broader framework of statistical collection on a national level and that the effective integration of livestock data, whether derived through broader agricultural surveys, administrative records, or one-off surveys, is essential for ensuring quality data which can feed into policy formulation or designing effective investments in the livestock sector.